HUBUNGAN KUALITAS SISTEM PEMBELAJARAN DENGAN PEMAHAMAN MATERI (Studi Kasus Pada Mahasiswa Manajemen UNISBA) - Denok Wahyudi Setyo Rahayu (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2015)
This study investigates correlation between instructional system and understanding of teaching materials. The study used correlational design, observing instructional system to indicate service quantity and understanding of teaching materials as costumer satisfaction. Sample of the study was 50 students of Management Program at UNISBA in the year 2014/2015. Data were analyzed using pie chart, a circle diagram dividing rate percentage of its elements. The study revealed that good instructional system provides good attainment of students. Results of pie chart 1 to pie chart 3, respectively showed: (1) Chart 1 Direct Evidences: good = 60% good, fair = 20%, less = 10%, and poor = 10% poor; (2) Chart 2 Responses: good = 65%, fair = 15%, less = 10%, and poor = 10%; (3) Chart 3 Costumer Satisfaction: good = 65%, fair = 20%, less = 10%, poor = 5%. In summary, good instructional system significantly relates to understanding of teaching materials.